Evaluasi Implementasi Akuntansi Pemerintah Berbasis Akrual Pada Laporan Keuangan Bawaslu Kab. Pulau Morotai Tahun Anggaran 2018 - Ardin Umar; Jamiludin Hasan; Selfine Katiandagho (Peneliti.net, 2021)
The enactment of Law No. 17/2010 on Accrual-based Government Accounting Standards (SAP) brought major changes in the financial reporting system in Indonesia. The changes are expected to provide a complete picture of the financial position. This research aims to find out the effectiveness of the implementation of accrual-based government accounting standards in Bawaslu's Financial Statements, Pulau Morotai Budget Year 2018. The data in this study were collected through observation methods, interviews, and documentation directly related to the implementation of Government Accounting Standards (SAP) based on accruals. Data source in the form of Bawaslu’s Financial Report in Pulau Morotai. The data that has been collected is then analyzed and interpreted in a narrative manner using qualitative analysis methods. The results of the study showed that in general the statements of Pulau Morotai in 2018 has implemented accrual-based financial reporting standards according to government regulation number 71 of 2010 concerning government accounting standards